MP022: Anticoagulation use in patients with atrial fibrillation/flutter in Canadian emergency departments since the introduction of the novel anticoagulants. (2nd June 2016) - Meshkat, N.; Leblanc, K.; Villalobos, D.; Lebovic, G.; Bhatia, S.; Dorian, P.
Abstract : Introduction: Despite strong evidence that antithrombotic drugs in atrial fibrillation/flutter (AF) patients reduce stroke risk, previous emergency department (ED) pre-novel anticoagulant (NOAC) studies have shown that most discharged patients are not optimally treated. This study sought to determine baseline antithrombotic management in AF patients, and appropriate antithrombotic prescription upon ED discharge since the introduction of NOACs.Methods: Consecutive AF patients discharged by the ED physician from three academic EDs in Toronto, Canada were retrospectively identified using ECG data. Primary AF was defined as AF in patients ≥18 years without congenital heart disease or other acute medical conditions. All management and disposition decisions were left to the discretion of the emergency doctor.Results: From July 2012 to October 2014, 691 patients with primary AF were identified. Of these, 34.4% (n=238) had new onset AF and 66.4% (n=459) were discharged home directly from the ED. Of those with previously known AF (n= 453), 44.2% (n=200) were on anticoagulation at ED arrival (warfarin 59.5%, dabigatran 23.0%, rivaroxaban 11.5%); 25.6% (n=116) on antiplatelets, and 29 (6.4%) on both. Based on 2012 Canadian AF guidelines, 60.1% of those who should have received anticoagulation were receiving it. In discharged patients meeting de novo criteria for anticoagulation (n=130), 20.0% (n=26) were started on anticoagulation and 23.1% (n=30) on antiplatelets. In patients with CHADS2 score ≥ 2 (n=61), 26.2% (n=16) were started on anticoagulation. Warfarin (73.1%) was most commonly prescribed followed by dabigatran (15.4%) and rivaroxaban (11.5%). Age was the only inverse independent predictor for appropriate anticoagulation (OR 0.92 per 5 year of age 95% CI 0.89-0.95, p <0.0001) i.e. older patients were less likely to be anticoagulated. The CHADS2 score was not an independent predictor of appropriate anticoagulation.Conclusion: Our study shows a persistent gap in the antithrombotic treatment of ED AF patients irrespective of their risk.